DESIGN AND IMPLEMENTATION INTERNET OF THINGS (IOT) ANDROID REMOTE-CONTROLLED QUADCOPTER - Budi Berlinton Sitorus (Jurnal Informatika dan Bisnis, 2019)
This Internet of Things (IoT) is leading the path to the smart world with ubiquitous computing and networking to ease different tasks around users and provide other tasks, such as easy monitoring of different phenomena surrounding us. In this research, a Wi-Fi controlled remote quadcopter is designed and built, enhanced with computing and communication technologies and join the communication framework, meeting a variety of services based on machine-to-machine interactions using wired and wireless communication. A quadcopter can be made several ways, one of them is using a simple microcontroller. In this research, Remote quadcopter is built by components such as 2300KV brushless motor, 2 pairs of the propeller, 4 ESCs, 11mAh LippoBaterry, Gyro+accelerometer board, and other quadcopter components. As the controller to the quadcopter, the Arduino Uno R3 module is utilized. The results of the research are a remote quadcopter controlled by an Android Smartphone as a combination of Arduino UNO and Wi-Fi module. The current results open many possibilities for future development for features of the quadcopter. Keywords: IoT, Remote quadcopter, Arduino